The Influence of Industrial Internship Programs on the Managerial Competency of Automotive Engineering Students - Baharuddin, Siti Ruqaiyah; Jumadin, Jumadin (PINISI Discretion Review, 2025)
This study aims to determine the influence of industrial internship programs on the managerial competence of Automotive Engineering students. The managerial competencies in question include the ability in work planning, organizing, leadership, decision-making, and work evaluation. This study uses a quantitative approach with an explanatory research method. Data were collected through a Likert scale-based questionnaire and analyzed using normality tests, Pearson correlation, as well as simple linear regression with the help of SPSS applications. The results of the study showed that the internship program had a positive and significant influence on students' managerial competence, with a correlation coefficient value of 0.774 and a significance of 0.000. Regression analysis showed that 59.9% of the variation in managerial competence could be explained by the internship program, with a regression coefficient of 1.021 (p < 0.001). These findings show that involvement in internship programs makes a real contribution to the development of managerial skills of Automotive Engineering students. Thus, the industrial internship program has proven to be one of the effective strategies in preparing students to face the world of work that demands technical and managerial skills in a balanced manner. Therefore, universities are advised to strengthen the design of internship programs through intensive cooperation with industry.